L' immaculée Conception à Séville et la fondation sacrée de la monarchie espagnole - Prosperi, Adriano 1939- (2007)
This paper first deals with the theological intentions of the doctrine of the Immaculate Conception in the Middle Ages, and continues to demonstrate that the decisive phase of the triumph of this doctrine took place in Spain in the first third of the seventeenth century. It was vigorously sustained by the Franciscans against the Dominicans, who were "maculist", celebrated with great pomp in Sevilla, and supported by Philip III in 1616. So religious absolutism served the interests of the new Spanish monarchy.
Keywords: Theologiegeschichte; Unbefleckte Empfängnis; Mittelalter; Spanien